Pigment Epithelium Derived Factor Is Involved in the Late Phase of Osteosarcoma Metastasis by Increasing Extravasation and Cell-Cell Adhesion - Kuriyama, Sei; Tanaka, Gentaro; Takagane, Kurara; Itoh, Go; Tanaka, Masamitsu (Frontiers in Oncology, 2022)
Organ tropism of metastatic cells is not well understood. To determine the key factors involved in the selection of a specific organ upon metastasis, we established metastatic cell lines and analyzed their homing to specific tissues. Toward this, 143B osteosarcoma cells were injected intracardially until the kidney-metastasizing sub-cell line Bkid was established, which significantly differed from the parental 143B cells. The candidate genes responsible for kidney metastasis were validated, and SerpinF1/Pigment epithelium derived factor (PEDF) was identified as the primary target. Bkid cells with PEDF knockdown injected intracardially did not metastasize to the kidneys. In contrast, PEDF overexpressing 143B cells injected into femur metastasized to the lungs and kidneys. PEDF triggered mesenchymal-to-epithelial transition (MET) in vitro as well as in vivo. Based on these results, we hypothesized that the MET might be a potential barrier to extravasation. PEDF overexpression in various osteosarcoma cell lines increased their extravasation to the kidneys and lungs. Moreover, when cultured close to the renal endothelial cell line TKD2, Bkid cells disturbed the TKD2 layer and hindered wound healing via the PEDF-laminin receptor (lamR) axis. Furthermore, novel interactions were observed among PEDF, lamR, lysyl oxidase-like 1 (Loxl1), and SNAI3 (Snail-like transcription factor) during endothelial-to-mesenchymal transition (EndoMT). Collectively, our results show that PEDF induces cancer cell extravasation by increasing the permeability of kidney and lung vasculature acting via lamR and its downstream genes. We also speculate that PEDF promotes extravasation via inhibiting EndoMT, and this warrants investigation in future studies.